NEKROLISIS EPIDERMAL TOKSIK PADA LANSIA : LAPORAN KASUS - Diana Silvi Nafila; Nikmatur Rosidah; Nanang Heru Sumarsono (Jurnal Ilmiah Fisioterapi, 2023)
The purpose of this case study is to report on physiotherapy interventions that can be given for toxic epidermal necrolysis in the elderly after taking NSAIDs. Physiotherapy interventions consist of active and passive Range of Motion (ROM) exercises to increase range of motion in all body regions, breathing exercises with deep breathing techniques to relax the respiratory muscles and improve pulmonary ventilation function and positioning exercises to reduce complications caused by immobilization and can increase comfort because it can reduce the pressure that persists on some parts of the body due to a static position. Physiotherapy examinations were measured and written to determine the patient's condition before intervention. In TEN conditions, physiotherapy can contribute to the incidence of TEN for physical rehabilitation to prevent the patient's body function from decreasing.